HIV-related high-risk behaviors among Chinese migrant construction laborers in Nantong, Jiangsu. - Xun Zhuang; Zunyou Wu; Katharine Poundstone; Changqing Yang; Yaqin Zhong; Shengyang Jiang (PLoS ONE, 2012)
HIV transmission in rural areas of China is being fueled in part by migrant workers who acquire HIV outside of their hometowns. Recent surveillance statistics indicate that HIV prevalence among returning migrants has increased significantly.We conducted a community-based cross-sectional study to assess HIV-related knowledge, attitudes and behaviors among migrant returnees in Nantong, Jiangsu Province, one of the largest exporters of migrant laborers.A total of 1625 subjects were enrolled with a response rate of 89%. All participants were male and of the majority Han ethnicity. The mean age was 39.0 years (SD = 6.7; range: 18 to 63), and most had a stable partner (N = 1533, 94.3%). Most correctly identified the major modes of HIV transmission (68.9%-82.0%), but fewer were able to identify ways that HIV cannot be transmitted. Nearly one-third of participants held positive attitudes toward having multiple sex partners, and nearly half believed that sex work should be legalized. Multiple logistic regression analysis indicated that risky sexual behavior (defined as sex with a casual or commercial sex partner) was associated with no stable partner; working abroad; correct condom use; age <22 at first sex; higher coital frequency; and having a positive attitude towards multiple sex partners.We found high levels of reported sex with a casual or commercial sex partner and low levels of consistent condom use. HIV prevention interventions among migrant workers need to focus on younger migrants, migrants without stable partners, and migrants who travel abroad for work.